Pentingnya nilai informasi laporan keuangan pada bisnis halal di Pondok Pesantren Kota Palembang - Maimunah, Mutiara; Febriany, Novita (Department of Accounting, Faculty of Business, Universitas PGRI Yogyakarta, 2020)
This study aims to analyze and determine the influence of organizational culture, human resource capacity, and the use of information technology on halal business on the value of financial statement information in Palembang Islamic boarding school. This type of research is quantitative research. The population in this study were all Islamic boarding schools in Palembang. The sampling technique uses saturated sampling technique. Data collection techniques using survey techniques by distributing questionnaires that contain a list of questions to respondents directly and data analysis techniques used are multiple regression analysis techniques. The results showed that organizational culture, human resource capacity, and the use of information technology had a positive effect on the value of financial statement information.